Higher thyroid hormone has a negative association with lower limb lean body mass in euthyroid older adults: Analysis from the Baltimore Longitudinal study of aging - Ibad, Hamza Ahmed; Mammen, Jennifer S.; Simonsick, Eleanor M.; Kwoh, C. Kent; Guermazi, Ali; Demehri, Shadpour (Frontiers in Aging, 2023)
Background: Hyperthyroidism is associated with lower lean body mass, as a result of catabolic actions of thyroid hormone. Therefore, higher thyroid hormone levels could be a factor in the development of sarcopenia and age associated functional decline. The relationship between thyroid hormone and muscle mass in ambulatory, euthyroid older adults is not known. Method: We used mixed-effects models to estimate the cross-sectional relationships (accounting for inter-person variability) between thyroid axis hormone measures and lower limb composition or sarcopenia at visits in the Baltimore Longitudinal Study of Aging (BLSA) at which DEXA scans were available and both thyrotropin (TSH) and free thyroxine (FT4) were in the reference range. Analyses were adjusted for levothyroxine use, age, race, sex, BMI, smoking, alcohol intake, cholesterol, and systolic blood pressure. Results: 1442 euthyroid participants (median age 68, 50% female, and 69% white) contributed to 5306 visits from 2003-2019. FT4 was negatively associated with lower limb lean mass (beta:-88.49; 95% Confidence Interval (CI):-122.78, -54.20; p<0.001) and positively associated with sarcopenia (OR: 1.11, 95% CI: 1.01, 1.22) in the whole cohort. Additionally, higher FT4 was associated with lower leg lean mass (beta:-66.79; 95% CI:-102.24, -31.33; p<0.001) and sarcopenia (OR:1.09, 95% CI:1.01, 1.18) in older adults, but not in younger adults alone. Conclusion: In euthyroid older adults, higher FT4 is associated with lower leg lean mass and higher odds of sarcopenia. Understanding the relationship between thyroid hormone and sarcopenia is needed to improve clinical decision-making and avoid functional decline from excess thyroid hormone use in older adults.